Risk of unintentional injuries in children and adolescents with ADHD and the impact of ADHD medications: A systematic review and meta-analysis. (January 2018) - Ruiz-Goikoetxea, Maite; Cortese, Samuele; Aznarez-Sanado, Maite; Magallón, Sara; Alvarez Zallo, Noelia; Luis, Elkin O.; de Castro-Manglano, Pilar; Soutullo, Cesar; Arrondo, Gonzalo
Highlights: Risk of injury in children and adolescents with ADHD is increased. ADHD medications reduce this risk. Results were robust to sensitivity analyses. Study was pre-registered in PROSPERO and reporting guidelines were followed. Abstract: A systematic review with meta-analyses was performed to: 1) quantify the association between ADHD and risk of unintentional physical injuries in children/adolescents ("risk analysis"); 2) assess the effect of ADHD medications on this risk ("medication analysis"). We searched 114 databases through June 2017. For the risk analysis, studies reporting sex-controlled odds ratios (ORs) or hazard ratios (HRs) estimating the association between ADHD and injuries were combined. Pooled ORs (28 studies, 4, 055, 620 individuals without and 350, 938 with ADHD) and HRs (4 studies, 901, 891 individuals without and 20, 363 with ADHD) were 1.53 (95% CI = 1.40, 1.67) and 1.39 (95% CI = 1.06, 1.83), respectively. For the medication analysis, we meta-analysed studies that avoided the confounding-by-indication bias [four studies with a self-controlled methodology and another comparing risk over time and groups (a "difference in differences" methodology)]. The pooled effect size was 0.879 (95% CI = 0.838, 0.922) (13, 254 individuals with ADHD). ADHD is significantly associated with an increased risk of unintentional injuries and ADHD medications have a protective effect, at least in the short term, as indicated by self-controlled studies.